2019
DOI: 10.1017/jie.2018.22
|View full text |Cite
|
Sign up to set email alerts
|

Sámi language teachers’ professional identities explained through narratives about language acquisition

Abstract: AbstractConducted in northern Finland, this study examines Sámi language teachers’ professional identities through their narratives of language acquisition. We focus on how teachers’ professional identities are shaped by their language acquisition process. The results are based on the narratives of nine North, Inari and Skolt Sámi language teachers. Two aspects of teachers’ narratives were significantly linked to their identities as Sámi language teachers: (1) their backgrounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…The position of teacher, a form of language role model, is not exclusively held by South Saami native speakers that grew up in a reindeer herding family and society, who could serve as the idealised native speaker in this context. These findings are in line with Hammine et al (2020), exploring Saami teachers' professional identity in the Inari, North and Skolt Saami areas, and with Pasanen (2018). They find that in the language revitalisation project of Inari Saami "some people working in professions essential for language transmission (like teachers) have no Inari Sámi background" (Pasanen, 2018, p. 370); the case of Inari Saami language revitalisation is viewed in the literature as a very good case of successful language revitalisation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The position of teacher, a form of language role model, is not exclusively held by South Saami native speakers that grew up in a reindeer herding family and society, who could serve as the idealised native speaker in this context. These findings are in line with Hammine et al (2020), exploring Saami teachers' professional identity in the Inari, North and Skolt Saami areas, and with Pasanen (2018). They find that in the language revitalisation project of Inari Saami "some people working in professions essential for language transmission (like teachers) have no Inari Sámi background" (Pasanen, 2018, p. 370); the case of Inari Saami language revitalisation is viewed in the literature as a very good case of successful language revitalisation.…”
Section: Discussionsupporting
confidence: 88%
“…Few studies have discussed LTI in Saepmie, and none in the South Saami part of Saepmie. For instance, Hammine et al (2020) explore Saami language teachers' professional identity, interviewing Skolt, Inari and North Saami teachers, many of them second-language learners, in the part of Saepmie overlapping Finland. They found that "non-indigenous teachers who have learned Sámi languages as adults actively link their roles as language teachers to the language revitalisation project" (p. 7).…”
Section: Theoretical Point Of Departure and Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The historical people of the Ryukyus have yet to be recognized as indigenous (Hammine, 2019a). Communal and academic efforts to, for instance, problematize the homogeneity narrative, document and discuss sociohistorical marginalization, address social, educational, and economic disparity within and transcending communities, and promote language revitalization in the Ryukyus, are occurring (albeit without the formal support of national government) (Anderson & Heinrich, 2014; Hammine, 2020).…”
Section: “Japan” and “Japaneseness” (?): Narrativesmentioning
confidence: 99%